Prenatal whole exome sequencing detects a new homozygous fukutin (FKTN) mutation in a fetus with an ultrasound suspicion of familial Dandy–Walker malformation. Issue 1 (22nd November 2019) - Traversa, Alice; Bernardo, Silvia; Paiardini, Alessandro; Giovannetti, Agnese; Marchionni, Enrica; Genovesi, Maria Luce; Guadagnolo, Daniele; Torres, Barbara; Paolacci, Stefano; Bernardini, Laura; Mazza, Tommaso; Carella, Massimo; et al.
Abstract: Background: Posterior fossa malformations are among the most diagnosed central nervous system (CNS) anomalies detected by ultrasound (US) in prenatal age. We identified the pathogenic gene mutation in a male fetus of 17 weeks of gestation with US suspicion of familial Dandy–Walker spectrum malformation, using Next Generation Sequencing approach in prenatal diagnosis. Methods: Whole exome sequencing (WES) approach has been performed on fetal genomic DNA. After reads preprocessing, mapping, variant calling, and annotation, a filtering strategy based on allelic frequency, recessive inheritance, and phenotypic ontologies has been applied. A fetal magnetic resonance imaging (MRI) at 18 weeks of gestation has been performed. An in silico analysis of a potential causative missense variant in the fukutin protein has been carried out through a structural modeling approach. Results: We identified a new homozygous missense mutation in fukutin gene ( FKTN, NM_006731.2: c.898G>A; NP_006722.2: p.Gly300Arg). Fetal MRI supported molecular findings. Structural modeling analyses indicated a potential pathogenetic mechanism of the variant, through a reduced activation of the sugar moieties, which in turn impairs transfer to dystroglycan and thus its glycosylation. These findings pointed to a redefinition of the US suspicion of recurrence of Dandy–Walker malformation (DWM) to a muscular dystrophy‐dystroglycanopathy type A4. Conclusions: The present case confirmed WES as a reliable tool for the prenatal identification of the molecular bases of early‐detected CNS malformations. Abstract : Prenatal diagnosis of central nervous system (CNS) anomalies following standard diagnostic procedures is challenging. Posterior fossa malformations are among the most diagnosed CNS anomalies detected by ultrasound in prenatal age. Whole exome sequencing (WES) approach on fetal genomic DNA and structural in silico analysis helped redefine a prenatal clinical suspicious of Dandy–Walker malformation to muscular dystrophy dystroglycanopathy Type A through the identification of a new fukutin homozygous missense mutation (NM_006731: c.898G>A; NP_006722.2: p.Gly300Arg). Prenatal diagnosis in cases of nonspecific or early‐detected CNS phenotypes can be lengthy and difficult. Multidisciplinary diagnostic approach combining instrumental (high‐quality fetal magnetic resonance imaging) and molecular analyses (WES) in fetuses with CNS structural anomalies could be a reliable approach.